Protist Collections: Essential for Future Research - d'Avila-Levy, Claudia M; Yurchenko, Vyacheslav; Votýpka, Jan; Grellier, Philippe (Trends in parasitology, 2016)
The vouchered deposit of protist type specimens in institution-maintained collections is a prerequisite for species description, and greatly enhances the chances of sample availability and preservation for future generations. However, specimens are currently most often deposited in personal collections maintained by the individual effort of researchers. We discuss the disadvantages of such a scenario and propose a change to this arrangement.
Keywords: taxonomy; Eukaryota; Parasitology; Research; voucher; parazitologie; odběr biologického vzorku; Specimen Handling; kinetoplastid; výzkum